Post-privatisation corporate performance in Poland: Evidence from companies privatized in 2008-2011 - Barbara Błaszczyk; Wiktor Patena (Center for Social and Economic Research (CASE), 2015)
The study concerns the effects of Polish privatisation program conducted in the years 2008-2011. After drawing a broad picture of this process we investigate the performance of 59 privatised companies, and finally focus on a deeper analysis of three companies, which is the core part of our study. We test the hypotheses that privatisation increases a company's profitability, labour productivity, capital investment spending, plow-back ratio and leverage. In case studies, we additionally explore the effect of privatization on each company's value. The outcomes concerning the larger group of companies are partly ambiguous (with four hypotheses confirmed and four rejected). Profitability has been not visibly improved, although a number of positive initiatives and improvements in performance occurred. By contrast, the three case studies showed a significant improvement of profitability and all other performance indicators observed, as well as a considerable increase of company value. Our results show that privatisation works, though its full effects need time to occur.
Keywords: G38; H27; L3; 330; privatisation; companies' performance; case study; state owned enterprises; DCF valuation